Prodrugs of dynemicin analogs for selective chemotherapy mediated by an aldolase catalytic Ab - Sinha, Subhash C. (National Academy of Sciences, 2004)
Prodrugs of dynemicin analogs were synthesized, and their activation by aldolase antibody (Ab) 38C2 was evaluated by DNA-cleaving activity, as well as tumor cell growth inhibition. Further, we provide evidence that the activated enediynes underwent covalent crosscoupling with the aldolase Ab, which appears to be a limiting factor of their tumor cell growth-inhibiting activity and should be of general interest in the field of enediyne chemotherapy. These findings might open new avenues for defined conjugations of small molecule drugs to mAbs in general and aldolase Abs in particular.